Previous open nephrolithotomy: Does it affect percutaneous nephrolithotomy techniques and outcome? - B. Lojanapiwat (2018)
Background and Purpose: The consequences of open nephrolithotomy are scar tissue around the kidney and in the retroperitoneum and distortion of the pelvicaliceal anatomy that may affect the techniques and outcome of percutaneous nephrolithotomy (PCNL). We compared the results and complications of patients undergoing PCNL who had and had not previously undergone open nephrolithotomy. Patients and Methods: A total of 178 calculi in 175 patients who had previously had open nephrolithotomy (group I) and 178 calculi in 175 patients who had never had a renal operation (group II) were treated with PCNL. The average time between open nephrolithotomy and PCNL was 8.5 years (range 4 months-22 years). In both groups, PCNL was done by a standard technique with serial Amplatz dilator enlargement of the tract to 30F. Upper-pole access under fluoroscopic guidance was done in most patients. The operative time, success rate, hospital stay, and complications in the two groups were compared. Results: The stone-free rates were 80.3% and 82.6% in groups I and II, respectively, and the rate of residual fragments ≤4 mm was 14.6% and 8.4%. The operative time, success rate, hospital stay, and complications did not differ significantly in the two groups. Conclusion: Percutaneous nephrolithotomy is effective and safe in patients who have previously had open nephrolithotomy with no more complications than are seen with PCNL of kidneys that have not been operated on. © Mary Ann Liebert, Inc.